2006
DOI: 10.1242/dev.02604
|View full text |Cite
|
Sign up to set email alerts
|

LONGIFOLIA1andLONGIFOLIA2, two homologous genes,regulate longitudinal cell elongation inArabidopsis

Abstract: Plants have diversified their leaf morphologies to adapt to diverse ecological niches. The molecular components responsible for regulating leaf morphology, however, have not been fully elucidated. By screening Arabidopsis activation-tagging lines, we identified a dominant mutant, which we designated longifolia1-1D (lng1-1D). lng1-1D plants were characterized by long petioles, narrow but extremely long leaf blades with serrated margins, elongated floral organs, and elongated siliques. The elongated leaves of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
123
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 33 publications
8
123
0
Order By: Relevance
“…Morphological and cellular analyses indicated that SLG7 has a function in regulating cell elongation in spikelets ( Figure 5). Similar to our data, LNG1 and LNG2 were also reported to play a positive role in increasing leaf and silique length through longitudinal cell elongation in Arabidopsis ( Lee et al 2006). These results suggested that the functions of SLG7 family members are probably conserved across monocots and dicots.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Morphological and cellular analyses indicated that SLG7 has a function in regulating cell elongation in spikelets ( Figure 5). Similar to our data, LNG1 and LNG2 were also reported to play a positive role in increasing leaf and silique length through longitudinal cell elongation in Arabidopsis ( Lee et al 2006). These results suggested that the functions of SLG7 family members are probably conserved across monocots and dicots.…”
Section: Discussionsupporting
confidence: 90%
“…The BLASTP analysis revealed that SLG7 shares numerous putative homologs (Figure 3), including two functionally characterized genes, LNG1 (At5g15580) and LNG2 (At3g02170), both of which function in the elongation of leaves, siliques, and seeds in Arabidopsis (Lee et al 2006). LNG2 (also named TON1 Recruiting Motif 1) is identified as a microtubule-associated protein, which is able to target TON1 to cortical microtubules (Drevensek et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 5B; Table III). LNG1 mutants affect leaf polar cell elongation in Arabidopsis (Lee et al, 2006). The previously characterized leaf-adaxialized kan1, kan2 double mutant produces finger-shaped protrusions on the abaxial surface (Pekker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Helical growth aberrations and altered leaf shape were reported for tomato sun lines (Wu et al, 2011) and often are associated with defects in MT functions (Buschmann et al, 2004;Ishida et al, 2007). Moreover, the growth defects are reminiscent of plants overexpressing LONGIFOLIA1/TON1 RECRUITING MOTIF2 (TRM2), which encodes a plant-specific MAP (Lee et al, 2006;Drevensek et al, 2012). Hence, the observed phenotypes point to roles of IQD16 in the regulation of MT arrays.…”
Section: Overexpression Of Iqd16 Alters Mt Organization and Cell Shapementioning
confidence: 99%